Assessment of Eustachian tube function in patients with tympanic membrane retraction and in normal subjects, - Canali,Inesângela (2017)
Abstract Introduction The diagnosis of Eustachian tube dysfunctions is essential for better understanding of the pathogenesis of chronic otitis media. A series of tests to assess tube function are described in the literature; however, they are methodologically heterogeneous, with differences ranging from application protocols to standardization of tests and their results. Objective To evaluate the variation in middle ear pressure in patients with tympanic membrane retraction and in normal patients during tube function tests, as well as to evaluate intra-individual variation between these tests. Methods An observational, contemporary, cross-sectional study was conducted, in which the factor under study was the variation in middle ear pressure during tube function tests (Valsalva maneuver, sniff test, Toynbee maneuver) in healthy patients and in patients with mild and moderate/severe tympanic retraction. A total of 38 patients (76 ears) were included in the study. Patients underwent tube function tests at two different time points to determine pressure measurements after each maneuver. Statistical analysis was performed using SPSS software, version 18.0, considering p-values <0.05 as statistically significant. Results Mean (standard deviation) age was 11 (2.72) years; 55.3% of patients were male and 44.7% female. The prevalence of type A tympanogram was higher among participants with healthy ears and those with mild retraction, whereas type C tympanograms were more frequent in the moderate/severe retraction group. An increase in middle ear pressure was observed during the Valsalva maneuver at the first time point evaluated in all three groups of ears (p = 0.012). The variation in pressure was not significant either for the sniff test or for the Toynbee maneuver at the two time points evaluated (p ≥ 0.05). Agreement between measurements obtained at the two different time points was weak to moderate for all tests in all three groups of ears, and the variations in discrepancy between measurements were higher in ears with moderate/severe tympanic retraction. Conclusion In this study population, the mean pressure in the middle ear showed significant variation only during the Valsalva maneuver at the first time point evaluated in the three groups of ears. Normal ears and those with mild retraction behaved similarly in all tests. The tested maneuvers exhibited weak to moderate intra-individual variation, with the greatest variation occurring in ears with moderate/severe retraction.